Larger Forms in Lophiotoma: Four New Species Described in the Philippines and Three from Elsewhere in the Indo-Pacific - Olivera, Baldomero (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
A group of venomous turriform gastropods in the subfamily Turrinae, genus Lophiotoma, has been investigated. Previously, forms in this group were identified as either Lophiotoma unedo or Lophiotoma indica. Our analysis has led to the description of four new species from the Philippines (L. bisaya, L. friedrichbonhoefferi, L. panglaoensis, and L. tayabasensis) and one each from Australia (L. capricornica), South Africa/Mozambique (L. dickkilburni), and Madagascar (L. madagascarensis). A new subspecies, L. indica queenslandica, is also described. In addition, 11 distinctive forms related to these taxa that may or may not deserve separate taxonomic status are defined; these need further evaluation. It is hypothesized that the forms of Lophiotoma discussed in this report are closely related to a particular subset of Gemmula, the G. kieneri/G. interpolata group.